2019
DOI: 10.1103/physrevb.99.085423
|View full text |Cite
|
Sign up to set email alerts
|

Many-body filling factor dependent renormalization of Fermi velocity in graphene in strong magnetic field

Abstract: We present the theory of many-body corrections to cyclotron transition energies in graphene in strong magnetic field due to Coulomb interaction, considered in terms of the renormalized Fermi velocity. A particular emphasis is made on the recent experiments where detailed dependencies of this velocity on the Landau level filling factor for individual transitions were measured. Taking into account the many-body exchange, excitonic corrections and interaction screening in the static random-phase approximation, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(188 reference statements)
0
6
0
Order By: Relevance
“…These schematics are drawn for ν ¼ 0; þ1, and þ2, with each of the four spin and valley levels shown explicitly, albeit with greatly exaggerated level shifts and gap sizes. In graphene, the inapplicability of Kohn's theorem implies the CR transition energies will reflect the single-particle LL separations plus many-particle shifts of the levels, along with excitonic and exchange corrections due to the excited electron and remnant hole [18][19][20]35,36]. Of course, the measured energies do not indicate which portion is due to level shifts vs exciton corrections.…”
Section: B Filling-factor Dependence Of Tmentioning
confidence: 97%
“…These schematics are drawn for ν ¼ 0; þ1, and þ2, with each of the four spin and valley levels shown explicitly, albeit with greatly exaggerated level shifts and gap sizes. In graphene, the inapplicability of Kohn's theorem implies the CR transition energies will reflect the single-particle LL separations plus many-particle shifts of the levels, along with excitonic and exchange corrections due to the excited electron and remnant hole [18][19][20]35,36]. Of course, the measured energies do not indicate which portion is due to level shifts vs exciton corrections.…”
Section: B Filling-factor Dependence Of Tmentioning
confidence: 97%
“…Presumably, when ν changes over a wide range as in Fig. 6, screening of the Coulomb potential v p will become important, as noted [33,34] for monolayer graphene. Via screening v p will get weaker with increasing |ν|, making the spectra decrease faster for larger |ν|.…”
Section: B Interband Resonance T3 ∼ T5mentioning
confidence: 92%
“…In experiment CR has been explored for monolayer [22][23][24] and bilayer [25,26] graphene. Many-body effects on CR [27][28][29][30][31][32][33][34] were first detected rather indirectly by a comparison of some leading intraband and interband resonances [22]. Recently, Russell et al [35] have reported a direct signal of manybody effects on CR in high-mobility hBN-encapsulated monolayer graphene; see also ref.…”
Section: Introductionmentioning
confidence: 99%
“…A key consequence of electron interactions in graphene is to renormalize the band velocity v → ṽ [6,[23][24][25]; in a magnetic field ṽ decreases weakly with increasing B, or at fixed field it is roughly constant when the lowest LL is partially filled and declines sharply as higher LLs become occupied [13]. Many-particle contributions have been seen in CR and magneto-Raman experiments [6,[11][12][13][14][15], and generally good agreement with theory has been found [8,9,17,18,26].…”
mentioning
confidence: 97%